Cadmium-induced oxidative stress and histological damage in the myocardium. Effects of a soy-based diet - Ferramola, Mariana Lucila (2012)
Cd exposure has been associated to an augmented risk for cardiovascular disease. We investigated the effects of 15 and 100ppm of Cd on redox status as well as histological changes in the rat heart and the putative protective effect of a soy-based diet. Male Wistar rats were separated into 6 groups and treated during 60days as follows: groups (1), (2) and (3) were fed a casein-based diet; groups (4), (5) and (6), a soy-based diet; (1) and (4) were given tap water; (2) and (5) tap water containing 15ppm of Cd2+; and (3) and (6) tap water containing 100ppm of Cd2+. Serum lipid peroxides increased and PON-1 activity decreased in group (3). Lipoperoxidation also increased in the heart of all intoxicated groups; however protein oxidation only augmented in (3) and reduced glutathione levels diminished in (2) and (3). Catalase activity increased in groups (3) and (6) while superoxide dismutase activity increased only in (6). Glutathione peroxidase activity decreased in groups (3) and (6). Nrf2 expression was higher in groups (3) and (6), and MTI expression augmented in (3). Histological examination of the heart tissue showed the development of hypertrophic and fusion of cardiomyocytes along with foci of myocardial fiber necrosis. The transmission electron microscopy analysis showed profound ultra-structural damages. No protection against tissue degeneration was observed in animals fed the soy-based diet. Our findings indicate that even though the intake of a soy-based diet is capable of ameliorating Cd induced oxidative stress, it failed in preventing cardiac damage.